Description of sandfly (diptera: Psychodidae: Phlebotominae) species from genus Sergentomyia (Franca and parrot, 1920) in Sri Lanka - Gajapathy, K.; Surendran, S.N. (Academic Journals Inc, 2012)
Leishmaniasis, mainly Cutaneous Leishmaniasis (CL), is a major public health concern in Sri Lanka. Although, the vector for any form of the disease is yet to be clearly discriminated in the country, a limited study reported the potential role of Phlebotomus argentipes s.l. in the transmission of Leishmania donovani, the causative agent of CL in Sri Lanka. In a survey from three Cutaneous Leishmaniasis (CL) endemic localities in Sri Lanka, a rich diversity of the genus Sergentomyia was discovered. Eleven species belong to three subgenera namely, Parrotomyia, Neophlebotomus and Grassomyia were identified and their detail morphology is described in this report. Only three species of Parrotomyia and one from each Neophlebotomus and Grassomyia have been reported previously from Sri Lanka. Eight species of Parrotomyia, namely Se. (Par.) rudnicki, Se. (Par.) babu insularis, Se. (Par.) modii, Se. (Par.) baghdadis, Se. (Par.) barraudi, Se. (Par.) grekovi, Se. (Par.) bailyi and Se. (Par.) species were recorded during the survey. Sergentomyia (Neophlebotomus) malayae, Sergentomyia (Grassomyia) dreyfussi turkestanica and Se. (Gra.) indica belong to the subgenera Neophlebotomus and Grassomyia were also recorded during this study. This is the first record for Sergentomyia (Neophlebotomus) malayae and Sergentomyia (Grassomyia) dreyfussi turkestanica and for all the species of Parrotomyia except Se. (Par.) babu insularis and Se. (Par.) barraudi. The study warrants for an extensive sandfly survey, especially in endemic areas, as Sergentomyia species are now considered as potential vectors for many parasites including Leishmania.
Keywords: Endemic; Leishmaniasis; Morphology; Sandflies; Sergentomyia